Early Miocene CO2 estimates from a Neotropical fossil leaf assemblage exceed 400 ppm. Issue 11 (12th November 2018) - Londoño, Liliana; Royer, Dana L.; Jaramillo, Carlos; Escobar, Jaime; Foster, David A.; Cárdenas‐Rozo, Andrés L.; Wood, Aaron
Abstract : Premise of the Study: The global climate during the early Miocene was warmer than the present and preceded the even warmer middle Miocene climatic optimum. The paleo‐CO2 records for this interval suggest paradoxically low concentrations (<450 ppm) that are difficult to reconcile with a warmer‐than‐present global climate. Methods: In this study, we use a leaf gas‐exchange model to estimate CO2 concentrations using stomatal characteristics of fossil leaves from a late early Miocene Neotropical assemblage from Panama that we date to 18.01 ± 0.17 Ma via 238 U/ 206 Pb zircon geochronology. We first validated the model for Neotropical environments by estimating CO2 from canopy leaves of 21 extant species in a natural Panamanian forest and from leaves of seven Neotropical species in greenhouse experiments at 400 and 700 ppm. Key Results: The results showed that the most probable combined CO2 estimate from the natural forests and 400 ppm experiments is 475 ppm, and for the 700 ppm experiments is 665 ppm. CO2 estimates from the five fossil species exhibit bimodality, with two species most consistent with a low mode (528 ppm) and three with a high mode (912 ppm). Conclusions: Despite uncertainties, it is very likely (at >95% confidence) that CO2 during the late early Miocene exceeded 400 ppm. These results revise upwards the likely CO2 concentration at this time, more in keeping with a CO2 ‐forced greenhouse climate.